ANALISIS POTENSI PERTUMBUHAN EKONOMI DAN PERGESERAN STRUKTUR PEREKONOMIAN DI KABUPATEN PANGKEP - Bahruddin, Bahruddin; Ladung, Fajar; Asrindah, Asrindah (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Parepare, 2022)
Each region in Indonesia has different characteristics or characters, it is influenced by the competitive advantage and economic potential of each region. The purpose of this study is to identify the basic sector and potential sectors that have competitive advantages to be developed in Pangkep Regency, as well as suggestions or information in the consideration of economic development planning in Pangkep Regency. This study uses secondary data, in the form of time series from the GRDP of Pangkep Regency and GRDP of South Sulawesi Province for the 2015-2019 period. The data analysis techniques used in this research are Location Quentient (LQ), Shift Share, and Klassen Typology. The results of the Location Quentient (LQ) analysis show that there are two basic sectors in Pangkep Regency. From the results of the Shift Share analysis, it is known that there are eight economic sectors that are classified as advanced, growing rapidly, and competitively. Meanwhile, from the Klassen Typology analysis, it is known that in Pangkep Regency there is one economic sector classified as Quadrant I, there is one sector belonging to Quadrant II, then there are eleven sectors belonging to Quadrant III, and there are four sectors belonging to Quadrant IV.